Влияние капиллярных сил на спекание при высоком давлении алмазных микро- и нанопорошков - Бочечка, А.А.; Назарчук, С.Н.; Гаврилова, В.С.; Романко, Л.А.; Белявина, Н.Н.; Черниенко, А.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
It has been shown that during sintering of diamond powders the summation of Laplace pressure and external pressure acting on a system is not observed. The modeling of the pore shape has shown that the cases are possible where the capillary forces are directed against the external forces acting on the system. The equation describing a limiting compaction of diamond particle system under high pressure and temperature in such case has been suggested. Experimental values of the density of diamond polycrystals sintered from diamond powders of various dispersity are well described by the specified equation within the measurement error. To improve the sintering, it is necessary to find additives, which would form chemical compounds with carbon and thus bound diamond nanoparticles in sintering.